Piezoresponse force microscopy of BaTiO3-chitosan and BaTiO3-polyethylene glycol nanocomposites - Silva L.M.A. (2021)
The work was funded by Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica-CONCYTEC according to agreement at Sub project 072–2018–FONDECYT–BM–IADT–AV.